Elder Nutrition - Linda B Bobroff; Martie Gillen (EDIS, 2018)
Older Floridians, their families, and communities face many issues related to aging. This 8-page fact sheet focuses on the way aging affects nutrition and diet, and choices that older adults can make to improve or maintain their health and well-being as they age. Written by Linda B. Bobroff and Martie Gillen, and published by the UF/IFAS Department of Family, Youth and Community Sciences, revised March 2018. http://edis.ifas.ufl.edu/fy628